Fatal intoxication with tianeptine (Stablon®) - Proença, Paula (2007)
Tianeptine (Stablon®), although structurally similar to tricyclic antidepressants, acts by enhancing the reuptake of serotonin. A fatal case is presented involving a 26-year-old man, found lying in bed with a "mushroom of foam" around his mouth. Empty blister packs of Stablon® and a suicide note were found next to the body. A liquid-liquid extraction procedure with n-hexane: ethyl acetate and n-hexane: 2-propanol, followed by LC-DAD-MS analysis, using positive mode electrospray ionization was performed. The detection limit was 0.001 [mu]g/mL. The toxicological results revealed the following tianeptine concentrations in the post-mortem samples: blood 5.1 [mu]g/mL; urine 2.0 [mu]g/mL; liver 23 [mu]g/g; stomach contents 22 mg. Femoral blood analyses also revealed an ethanol concentration of 0.53 g/L. The present method was also developed and validated for the other post-mortem specimens, since no previous published data had confirmed the post-mortem distribution of tianeptine. The absence of other suitable direct causes of death (macroscopic or histological) and the positive results achieved with the toxicological analysis led the pathologist to rule that death was due to an intoxication caused by the suicidal ingestion of tianeptine in combination with alcohol.